Participatory Monitoring and Evaluation, Power Dynamics and Stakeholder Participation : analysing Dynamics of Participation Between World Vision and its Stakeholders in Thusalushaka Area Development Programme PM & E - Thebe, Vusilizwe (University of Pretoria, 2019)
Dissertation (MSocSci)--University of Pretoria, 2018.